Japanese manners & ethics in business - Mente, Boye De (East Asia Pub. Co., 1966)
This book is not just a recounting of the raunchy bachelor activities of the author, it also reveals a great deal about the cultural attitudes and behavior of the Japanese during this time-frame. It therefore has "socially redeeming value" as well as being a provocative read.